Survival of Bacterial Strains on Wood (Quercus petraea) Compared to Polycarbonate, Aluminum and Stainless Steel - Ju-Chi Chen; Muhammad Tanveer Munir; Florence Aviat; Didier Lepelletier; Patrice Le Pape; Laurence Dubreil; Mark Irle; Michel Federighi; Christophe Belloncle; Matthieu Eveillard; Hélène Pailhoriès (MDPI AG, 2020)
Healthcare-associated infections (HAI) remain a burden in healthcare facilities, environmental surfaces being a potential reservoir for healthcare-associated pathogens. In this context, exploration of materials with potential antimicrobial activities represents a way forward for the future. Here, we explored the survival of four bacterial species commonly involved in HAI (Acinetobacter baumannii, Enterococcus faecalis, Klebsiella pneumoniae, Staphylococcus aureus), on oak versus three other materials (aluminum, polycarbonate, stainless steel). Twenty microliters of each bacterial suspension (approximatively 107 bacteria) were deposited on each material. Bacterial counts were measured by grinding and culturing on day 0, 1, 2, 6, 7 and 15. Analyses were performed in triplicate for each material and each time evaluated. It appeared that the bacteria viable count decreased rapidly on transversal and tangential oak compared with the other materials for all bacterial species. Furthermore, no difference was noticed between transversal and tangential oak. These results underline the potential for use of oak materials in healthcare facilities, a consideration that should be supported by further investigations.